A Recursive Approach to Solving Parity Games in Quasipolynomial Time - Lehtinen, Karoliina; Parys, Paweł; Schewe, Sven; Wojtczak, Dominik (Logical methods in computer science, 2022)
Zielonka's classic recursive algorithm for solving parity games is perhaps the simplest among the many existing parity game algorithms. However, its complexity is exponential, while currently the state-of-the-art algorithms have quasipolynomial complexity. Here, we present a modification of Zielonka's classic algorithm that brings its complexity down to $n^{O\left(\log\left(1+\frac{d}{\log n}\right)\right)}$, for parity games of size $n$ with $d$ priorities, in line with previous quasipolynomial-time solutions.